Cardio Protective Effect of Ethanolic Extract Vernonia Amygdalina Delile on Rats Induced L-NAME - Harahap, Rizki Doli Hartama; Harahap, Urip; Dalimunthe, Aminah (Jurnal Ners, 2024)
This study aimed to analyse the effects of ethanol extract of African leaves (Vernonia Amygdalina Del.) on the levels plasma renin, IL-6 and cardiac histopathology in L-NAME-induced rats. This research stage includes the preparation of ethanol extract of African leaves, standardization of extracts and testing the effectiveness of African leaves on rat heart damage. Data were analysed using one-way ANOVA with p<0.05. testing the cardioprotective effectiveness of ethanol extract of African leaves in hypertension model rats and then examining heart histopathology using HE staining and analysing parameters, namely plasma renin and IL-6 levels. This study used 6 groups, each group consisted of 5 male rats, namely the normal group, negative control by administering L-NAME 40 mg/kgBB, positive control by administering L-NAME plus lisinopril 2.5 mg/kgBB, EEDA 100 mg/kgBB, EEDA 300 mg/kgBB and EEDA 500 mg/kgBB. L-NAME responds to heart damage such as degeneration and necrosis of heart cells. In the negative group, plasma renin levels were 40.60 ± 9.98 ng/mL while the EEDA group with a dose of 500 mg/kgBB experienced the highest decrease in plasma renin compared to other EEDA groups and positive controls, namely 13.80 ± 1.30 ng/mL. The positive control group obtained plasma renin levels of 14.20 ±1.79 ng/mL. In the negative group, IL-6 levels were 4.80 ± 1.30 pg/mL while the group given EEDA, the group with a dose of 500 mg/kgBB experienced a decrease in IL-6, namely 1.52 ±0.96 ng/mL. The positive control group experienced a decrease in IL-6 levels of 0.77 ± 0.20 ng/mL. The result can be concluded that EEDA reduces plasma renin, IL-6 levels, improves the condition of cardiac cell degeneration and necrosis.